Understanding of Reading Literacy of Z Generation in the Digital Era: Evidence from North Sulawesi - Manggopa, Hiskia Kamang; Kumampung, Deislie R. Henrieta; Batmetan, Johan Reimon (JR Education, 2022)
Literacy plays a very important role in life every day like the need gets information. User information as much as possible will respond to various information received especially information from digital media. This study aims to analyze now literacy read Z generation in Sulawesi north. The method used is method quantitative with a descriptive approach. Study this conducted with the Z generation sample in North Sulawesi. The results of this research in is showing that exists the phenomenon of the Z Generation in North Sulawesi always responds to various information that appears in digital mass media. Research results also show that the Z generation in North Sulawesi is very vulnerable and provocative from the information they get because of a lack of literacy reading so that still many Z Generation are affected as well as follow take a role in disseminating the information it contains news hoax. Studies conclude that literacy reading by Z Generation plays a very important role in increasing interest in literacy reading by using the information obtained from digital media and each other share about culture literacy good read so that no already affected news hoaxes.